Free Vibrations of Thin, Elastic, Orthogonally Stiffened Shells of Revolution with Stiffeners Treated as Discrete Elements - Błocka, B. (Engineering Transactions, 1989)
This paper presents the method and numerical examples of the calculation of free-vibration frequencies and modes of thin, elastic, orthogonally stiffened shells of revolution. The variational formulation has been employed. The integro-differential Hamilton functional is brought to the algebraic form by separation of the variables, then expanded into trigonometric series in the circumferential direction and discretized by the finite difference scheme in the meridional direction. The three calculation models are compared: a shell with stringers modelled by a smooth orthotropic shell, a shell with stringers treated as discrete elements without couplings between harmonics and with the couplings. It is shown that taking couplings into account may influence the frequencies and modes calculated. The results obtained are compared with experimental ones published in the literature.